Péptido y hemoglobina Glicosilada como métodos de control metabólico en adultos mayores diabéticos tipo 2 del Hospital IESS- Machala. - Romero Alvarado, Norman Geovanny (2015)
Background: Type 2 diabetes is a heterogeneous and progressive disease characterized by insulin resistance and secretion problems. In the diabetic elderly it is important to achieve a good metabolic control, which then allows the patient to reach the established level for each of the parameters in the risk of developing chronic complications such as blood glucose and glycosylated hemoglobin targets. Objective: To determine the level of metabolic control in type 2 diabetic elderly Hospital IESS-Machala. Material and methods: This descriptive study was conducted in 50 elderly diabetics treated at the Department of Geriatrics Hospital IESS-Machala, samples were obtained under biosafety standards, quality control and processed in the particular clinical laboratory. The results were recorded into the computer and analyzed using SPSS and Microsoft Excel program.